The Analysis of Figurative Language in the “Doo-Wops & Hooligans” Album by Bruno Mars - Putri Wirastuti, I Gusti Agung; Ayu Inkayanti, Ni Putu; Dera Sintya Eka Suputri, Ni Putu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2025)
This paper analyzes the figurative language used in five popular songs by Bruno Mars from his first album: “Grenade,” “Just the Way You Are,” “The Lazy Song,” “Talking to the Moon,” and “Marry You.” Figurative language is important in songs because it helps express deep emotions and ideas. In “Grenade,” the singer uses hyperbole, metaphor, and symbolism to show the pain of one-sided love. He says things like “I’d catch a grenade for you” to show strong sacrifice. In “Just The Way You Are,” he uses simile, metaphor, and repetition to show love and admiration, comparing the girl’s beauty to stars and affirming she is perfect as she is. “The Lazy Song” employs casual, humorous imagery and repetition to convey feelings of relaxation and rebellion against responsibilities. “Talking to the Moon” uses metaphor and imagery to express loneliness and longing for connection. “Marry You” uses playful metaphor and repetition to express spontaneous love and commitment. All five songs use figurative language to enhance emotional impact and poetic beauty. This analysis shows how Bruno Mars’s use of figurative expressions creates strong feelings in listeners and helps deepen their understanding of the songs’ meanings.